2008
DOI: 10.1111/j.1749-4486.2008.01747_12.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical techniques for the treatment of nasal valve collapse: a systematic review

Abstract: Objectives.  To critically evaluate the surgical treatment strategies for nasal valve collapse and their outcomes. Method.  A systematic review of studies for surgically treated nasal valve collapse from 1970 to 2006 including an analysis of techniques and their outcomes. Database search of EBM reviews, (Cochrane, DARE, CCTR & ACP Journal club), Medline and EMBASE’ including a hand search of bibliographies in identified papers. The outcomes used are success of techniques at relieving symptoms and cosmesis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 0 publications
3
62
0
3
Order By: Relevance
“…However, these patients were deemed to have EVD as their primary cause of their nasal obstruction on clinical assessment by 2 experienced rhinoplasty surgeons in line with consensus statements, and the correction of septal abnormalities and turbinate reduction was applied consistently across both groups. Objective outcomes following surgical management of EVD have historically been lacking in the literature 3,20 and have actually been discouraged or dismissed due to poor correlation with subjective measures. 21 This is in contrast to patientreported outcomes, which have been deemed more important and correlate well with patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, these patients were deemed to have EVD as their primary cause of their nasal obstruction on clinical assessment by 2 experienced rhinoplasty surgeons in line with consensus statements, and the correction of septal abnormalities and turbinate reduction was applied consistently across both groups. Objective outcomes following surgical management of EVD have historically been lacking in the literature 3,20 and have actually been discouraged or dismissed due to poor correlation with subjective measures. 21 This is in contrast to patientreported outcomes, which have been deemed more important and correlate well with patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and support of the alar cartilage may not seem compromised at first, but long-term stability as a result of contractile forces may cause weak cartilages to be at risk. 9,10 Herein, I describe the lateral crural setback in combination with a cephalic turn-in flap (LSCT) as a new technique for management of the drooping nose. I tried to preserve structural integrity of alar cartilage as much as possible in this technique.…”
mentioning
confidence: 99%
“…As a result, much of our knowledge in nasal valve surgery is based on retrospective reports. That being said, both Rhee et al [59] and Spielmann et al [10] found that despite the lack of level I data, there is good evidence that nasal valve surgery is beneficial for patients. In 2010, Rhee et al [6] proposed guidelines for treatment of nasal valve collapse based on available literature and expert consensus.…”
Section: Discussion/ebmmentioning
confidence: 99%
“…Clinicians use both the Cottle and modified Cottle maneuvers to diagnose NVC. [10] Attention should also be paid to hypertrophic turbinates, caudal septal deflections, and wide medial crural footplates.…”
mentioning
confidence: 99%